THE EFFECT OF SPECIFICITY OF ENCODING ON HUMAN MEMORY - Holmberg, Louise Marta (My University, 1982)
The thesis examines the effect that specificity of encoding has on human memory. Specificity of encoding is defined as the precision and detail of stimulus analysis required to fulfill the purpose of the encoding task. The memory trace is characterized as the description of the analysis used to interpret the stimulus event. Greater specificity of encoding influences the quality of the memory trace by requiring a more complete and specific description of the stimulus to differentiate the stimulus in the task environment. The resulting memory trace is more distinctive and generally is more accessible and more discriminable from alternative traces. The experiments presented demonstrate that specificity of encoding in itself is not sufficient to ensure increased memory performance. Experiment 1 demonstrates that specificity of encoding enhances cued recall and recognition, and the cohesion of the memory trace, when the increased specificity stresses semantic, but not structural, aspects of the stimulus. The differential effect of specificity is attributable to the specificity of encoding and not to the cognitive effort expended during encoding. Experiment 2 demonstrates that specificity of encoding may occur without an accompanying completeness of encoding, resulting in a relatively inaccessible (free recall), but cohesive, memory trace. Experiments 3 and 4 demonstrate that the potential distinctiveness of specific encoding may be masked by incongruity of encoding. Specificity of encoding results in a cohesive, retrievable memory trace. Despite the fact that incongruity interferes with specificity, such specificity may still result in higher recall than does a more general encoding for meaning. Experiment 5 demonstrates that the potential effects of specificity of encoding are severely undermined when incongruity leads to a superficial semantic encoding. Experiment 6 establishes that specificity of encoding is critical to the formation of a distinctive memory trace, but that the accessibility and discriminability of the trace may be hampered by a loss of specificity or completeness in the retrieval context. However, the cohesion of the memory trace is determined by the encoding and is not influenced by a change in context at the time of the memory test.
Keywords: Psychology; Psychology